The Development of Interactive Multimedia on The High School’s Nanotechnology - Trixie, Stefani; Cahyaning Ratri, Monica (Jurnal Pendidikan Kimia Indonesia, 2024)
The lack of learning resources and media on nanotechnology, a new topic in the High School Merdeka curriculum, is challenging for teachers. Therefore, high school students in Indonesia still need to use interactive multimedia in learning activities to help them understand the learning material. This research aims to (1) create products in the form of interactive multimedia that meet the eligibility criteria and (2) know students' responses to interactive multimedia. ADDIE development mode was used in this research. A total of 10 students in class X SMA Pangudi Luhur Sedayu were sampled in the limited trial. The results showed that: (1) the product has the eligibility criteria with average percentage of 88,7% fulfilled very feasible criteria; fulfilled very valid criteria with an average of 88,7%, fulfilled very effective criteria on an average of 87, fulfilled very practical criteria with an average of 89%; (2) the response of students to the product is very good and gets good comments. The developed interactive multimedia can support the nanotechnology learning process in senior high schools.